Social media use is associated with body image concern in young adults during the COVID-19 pandemic - Marina de Sá Azevedo; Brenda Esper-Pereira; Larissa Vaz-Gonçalves; Raquel Machado Schincaglia; Marília Mendonça Guimarães; Karine Anusca Martins; Luciana Bronzi de Souza (Jornal Brasileiro de Psiquiatria)
ABSTRACT Introduction: Body image is the mental image we form of our own body, and it can be influenced by several aspects of everyday life. Thus, the aim of this study is to examine the relationship between social media use and body image concerns among young adults during the COVID-19 pandemic. Methods: Cross-sectional study conducted with 461 young adults (18-30yrs), from Midwest Brazil, who answered an online and self-reported questionnaire to determine the social media use, with questions about time of service, frequency of access, and media influence on behaviors. The Body Shape Questionnaire and Stunkard's Figure Rating Scale were also used. Sample was divided into two groups: some concerns about body image and weight (mild, moderate, or severe; SC, >110) and no concerns about body image and weight (NC, ≤110. All analyses were performed with a significance level of 5%. Results: 37.0% of participants showed body image concern and 85.9% body dissatisfaction. Instagram (93.71%) was the most popular social media platform. An association between social media use and a greater chance of developing body image concerns was observed in the following outcomes (p<0.05): body comparison (OR:157.22), social media influence on perception/body relation (OR:56.31), influence to "cut out" foods considered "unhealthy" (OR:10.66), follow diets (OR:7.13), follow profiles of diet (OR:6.46), and felt motivated to change aspects of their body (OR:6.14). Conclusions: Social media use was associated with negative outcomes on body image concerns in young adults during the COVID-19 pandemic.